Immune Checkpoint Inhibition for Triple-Negative Breast Cancer: Current Landscape and Future Perspectives - Yi, Huimei; Li, Ying; Tan, Yuan; Fu, Shujun; Tang, Faqing; Deng, Xiyun (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) is characterized by the lack of clinically significant levels of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Owing to the aggressive nature and the emergence of resistance to chemotherapeutic drugs, patients with TNBC have a worse prognosis than other subtypes of breast cancer. Currently, immunotherapy using checkpoint blockade has been shown to produce unprecedented rates of long-lasting responses in patients with a variety of cancers. Although breast tumors, in general, are not highly immunogenic, TNBC has a higher level of lymphocyte infiltration, suggesting that TNBC patients may be more responsive to immunotherapy. The identification/characterization of immune checkpoint molecules, i.e., programmed cell death protein 1 (PD1), programmed cell death ligand 1 (PDL1), and cytotoxic T lymphocyte-associated antigen 4 (CTLA4), represents a major advancement in the field of cancer immunotherapy. These molecules function to suppress signals downstream of T cell receptor activation, leading to elimination of cytotoxic T lymphocytes and suppression of anti-tumor immunity. For TNBC which has not seen substantial advances in clinical management for decades, immune checkpoint inhibition offers the opportunity of durable response and potential long-term benefit. In clinical investigations, immune checkpoint inhibition has yielded promising results in patients with early-stage as well as advanced TNBC. This review summarizes the recent development of immune checkpoint inhibition in TNBC, focusing on humanized antibodies targeting the PD1/PDL1 and the CTLA4 pathways.